2011
DOI: 10.3109/07357907.2011.616252
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Risk of Breast Cancer Recurrence in Patients Using ACE Inhibitors, ARBs, and/or Statins

Abstract: The use of ACE-inhibitors/ARBs, statins, and the combination of both were all associated with a reduced risk of breast cancer recurrence. This observation should prompt further exploration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
157
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(169 citation statements)
references
References 46 publications
9
157
2
1
Order By: Relevance
“…This finding is consistent with virtually all previously reported data (cancer-specific mortality: HR 0.73, 95% CI 0.59-0.92, P = 0.000; all-cause mortality: HR 0.72, 95% CI 0.58-0.89, P = 0.000). In addition, many articles have confirmed that the use of statins can reduce breast cancer incidence and the risk of recurrence [13,14], thus indicating the wide-ranging protective effects of statins in patients with breast cancer. However, the mechanism for how statins improve the prognosis of patients with cancer differs from that in the cardiovascular field.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with virtually all previously reported data (cancer-specific mortality: HR 0.73, 95% CI 0.59-0.92, P = 0.000; all-cause mortality: HR 0.72, 95% CI 0.58-0.89, P = 0.000). In addition, many articles have confirmed that the use of statins can reduce breast cancer incidence and the risk of recurrence [13,14], thus indicating the wide-ranging protective effects of statins in patients with breast cancer. However, the mechanism for how statins improve the prognosis of patients with cancer differs from that in the cardiovascular field.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these observations, GGTI treatment appears as a promising anti-CSC therapy. The use of statins, which inhibit MVA metabolism, reduces the risk of breast cancer recurrence [38,39]. This observation may be linked to the inhibition of CSCs.…”
Section: Discussionmentioning
confidence: 99%
“…No reduced risk was observed in users of hydrophilic statins. In 703 American women treated for stage II/III breast cancer between 1999 and 2005 and followed until 2008, users of statins (n = 156) had a reduced risk of recurrence in multivariate analysis (HR = 0.40, 95% CI, 0.24-0.67) (Chae, Valsecchi et al 2011). No effect was seen on overall survival.…”
Section: Breast Cancer Epidemiological Studies Showing a Higher Incimentioning
confidence: 89%